Neuroendocrine neoplasms of the sinonasal region. (18th July 2015) - Bell, Diana; Hanna, Ehab Y.; Weber, Randal S.; DeMonte, Franco; Triantafyllou, Asterios; Lewis, James S.; Cardesa, Antonio; Slootweg, Pieter J.; Stenman, Göran; Gnepp, Douglas R.; Devaney, Kenneth O.; Rodrigo, Juan P.; et al.
Abstract: Neuroendocrine neoplasms of the sinonasal region, which are relatively uncommon but clinically very important, are reviewed here in the light of current knowledge. Using a definition for neuroendocrine based on phenotypic, histologic, immunohistochemical, and electron microscopic features rather than histogenetic criteria, sinonasal neuroendocrine carcinomas are examined with a particular emphasis on the small‐cell and large‐cell subtypes. This is followed by revisiting olfactory neuroblastoma because it is also a tumor that shows a neuroendocrine phenotype. Kadish clinical and Hyams histologic grading systems as prognosticators of olfactory neuroblastoma are also considered in detail. Finally, controversies regarding sinonasal undifferentiated carcinoma as a neuroendocrine tumor are discussed and a possible relationship with high‐grade olfactory neuroblastoma is explored. Genetic events and current management of these tumors are also outlined. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E2259–E2266, 2016